The Influence of Tranexamic Acid on the Postabortion Period Course after Medical Abortion - Babenko O.; Bodunova T. (Львівський клінічний вісник)
Introduction. In the last decade, Ukraine followed all the developed countries with a radical change in the approaches to abortion due to medical abortion (MA). It has become a leading component of the safe abortion concept adopted by WHO. The course of the postabortion period differs somewhat from that after surgical termination of pregnancy. The main difference is the duration of bleeding (bloody discharge) after MA. Long menstrual bleeding is an expected consequence of MA. As a rule, bloody discharge gradually decreases within about 2 weeks after MA, but in some cases can persist up to 45 days. Nevertheless, many women regard this feature as a negative characteristic of the method and often ask the doctor for prescription drugs that can eliminate the discharge. One of the drugs from the first line of menstrual bleeding drugs in the world is tranexamic acid (TA). The aim of this study was to investigate the effectiveness of the TA in reduction of the blood loss and improvement of the quality of life in women after MA. Materials and methods. The research was conducted from January to December 2013 on the basis of the city clinical hospital N 17, in which a model clinic on safe abortion was established in 2010. The clinic was established in January. All women with ongoing vaginal bleeding10 days after MA were randomly divided into 2 groups: basic (45), which was prescribed TA and for the comparison – without this medication (41), which was monitored over time. The examination included a complete blood count, coagulation system observation, estimates of the total blood loss using piktoral charts and quality of life. These indicators were studied twice: on the 10th day after the abortion and on the 1st day of the first menstruation after abortion. Results. An analysis of the quality of life of the surveyed women revealed the differences between the groups at the end of the observation, whereas initially there were no such records, namely: women who had long periods of bloody discharge, assessed their physical functioning as well as the emotional and mental state (p <0.05).The study showed a significant decrease in the volume and duration of the blood loss, as well as improvement of the quality of life of women taking TA. At the same time, it should be noted that changes in the parameters of the coagulating system of blood have not been registered in women taking TA after the MA. Conclusions. Women experiencing discomfort in case of prolonged bloody discharge after MA can take TA as a safe and effective means.